TOLERANSI BERAGAMA PERSPEKTIF ISLAM DAN KONG HU CU - Taslim HM Yasin (Prodi Studi Agama-Agama, 2021)
Islam is a universal religion that regulates all aspects of life, including teachings about religious harmony. Normatively, the Koran has included verses related to religious pluralism, multiculturalism and tolerance of religious life. Historically the Medina pajamas are historical witnesses that the Prophet laid the foundation and became an example in living a life of different religions and cultures. For Muslims in Indonesia the elimination of seven words in the Jakarta pajamas is a tangible form of inter-religious harmony shown by Muslims. Likewise with the Confucian religion, there are teachings that can lead its adherents to live in harmony with other religions, among the teachings or five noble characteristics of Wu Chang, which are seen as the concept of teachings that can create a harmonious life. The two religions generally maintain harmony with each other, but in particular there are often misunderstandings such as reality shows that there are not a few actions that deviate from the values of tolerance. The method in this discussion uses a library research (library research), with a qualitative approach. The results of this discussion illustrate that Islam and Confucianism positively support the existence of tolerance between religious communities and the government. Furthermore, religious tolerance has limits that must be maintained and respected, for example in the form of the social interests of the two teachings, while regarding the creed, both are not allowed to tolerate. The similarity of tolerance according to both is the harmony of life between religious communities, which is something that is mentioned in the Al-Quran and the book of Lun Yu. Like mutual respect, please help and be fair to every people. Meanwhile, what distinguishes religious tolerance is that Islam does not allow marriage to a non-Muslim, while Confucianism allows marriage to people of different religions